A good birth : finding the positive and profound in your childbirth experience - Lyerly, Anne Drapkin (Avery, a member of Penguin Group (USA) Inc., 2013)
"Based on the author's landmark study in which she interviewed more than one hundred women about their childbirth experiences, this book provides narrative and information about how to make any birth a positive event"--